Developing a Browser Extension with AI for Website Classification - Nguyen, Van Vinh Toan (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Information Technology - Data Science and Artificial Intelligence; 2020 - 2025